2015
DOI: 10.1249/mss.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Training-Related Risk of Common Illnesses in Elite Swimmers over a 4-yr Period

Abstract: Particular attention must be paid to illness prevention strategies during periods of intensive training, particularly in the winter months or in case of the recent medical episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
118
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 26 publications
10
118
2
2
Order By: Relevance
“…Based on the results of the current study an increase of this amount in weekly or monthly TL would be accompanied by an increased illness risk of 50% and 54%, respectively. This is similar to studies in adult athletes which identified increased illness risk during times of increased weekly TL,26 28 29 31 and a recent systematic review which found a similar relationship in the majority of included studies of adult athletes 9. Our findings are also consistent with the only prior study of TL and illness in youth athletes of which we are aware found that increased training duration was associated with illness risk 24.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the results of the current study an increase of this amount in weekly or monthly TL would be accompanied by an increased illness risk of 50% and 54%, respectively. This is similar to studies in adult athletes which identified increased illness risk during times of increased weekly TL,26 28 29 31 and a recent systematic review which found a similar relationship in the majority of included studies of adult athletes 9. Our findings are also consistent with the only prior study of TL and illness in youth athletes of which we are aware found that increased training duration was associated with illness risk 24.…”
Section: Discussionsupporting
confidence: 90%
“…Few other studies have examined infection rates in athletes for periods of more than a few weeks or months. However, Hellard et al 11 reported a similar frequency of infectious infection for elite swimmers who experienced, on average, four episodes of respiratory, gastrointestinal and/or urogenital infection per person-year. Hence, it appears that elite endurance athletes experience broadly similar infection rates, regardless of whether their competition season falls during the winter or summer months.…”
Section: Discussionmentioning
confidence: 94%
“…However, cross-sectional studies indicate that individuals with high training loads experience a greater frequency of upper RTIs 9. Furthermore, longitudinal studies with athletes report an increased infection incidence during periods of intense training or competition 10 11. Malm12 suggested that, although high training loads may suppress immunity, becoming a successful elite athlete requires an immune system capable of withstanding infections even during severe physiological and psychological stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, o presente estudo objetivou investigar a dinâmica da CIT, da tolerância ao estresse (TE) e dos sintomas de infecção do trato respiratório superior (ITRS) em jovens ginastas durante períodos de treinamento sem competição e períodos de treinamento com competição. Uma vez que estudos anteriores mostraram redução na CIT nos períodos competitivos comparados aos períodos de treinamento (FREITAS et al, 2014;HELLARD et al, 2015), tem-se a hipótese de se observar maior CIT no período de treinamento sem competição, quando comparada ao período de treinamento com realização de competições. Em adição, espera-se que as respostas para a TE e ITRS sejam moduladas pelas alterações na CIT.…”
Section: Introductionunclassified